La innovación curricular en la Facultad de Medicina de la Universidad de Chile - Sepúlveda C, Cecilia (Revista Hospital Clínico Universidad de Chile, 2014)
This article describes the process of curricular innovation iniciated by the University of Chile Faculty of Medicine in 2006. It uses as a core document the “Educational Model of the University of Chile Faculty of Medicine”, published in 2012, where the main principles of the innovation are declared.